The Concept of “Red Culture” and Its Significance in Contemporary China - Shu , Dongxin (Research Developments in Arts and Social Studies Vol. 5, 2022)
This study looks at "red culture" from three perspectives: its origins, representations, and current relevance. It examines the conditions in which "red culture" emerged and evolved during China's democratic revolution, socialist construction, and reform and opening-up. "Red culture" refers to the "red legacies" and "red spirit" that have emerged during China's revolution, construction, and reform under the leadership of the Communist Party of China (CPC) in order to achieve national independence, economic progress, cultural prosperity, and national rejuvenation. Historical sites and a constellation of spirit represent the CPC's source of strength. In a globalized world, "red culture" assists the Chinese people in raising awareness of the need to maintain and promote great traditional Chinese culture while also guarding against cultural imperialism. It also provides impetus for the development of a strong cultural confidence and a rich, flourishing socialist culture with Chinese characteristics.